2018
DOI: 10.1002/cpt.1099
|View full text |Cite
|
Sign up to set email alerts
|

Clopidogrel Increases Dasabuvir Exposure With or Without Ritonavir, and Ritonavir Inhibits the Bioactivation of Clopidogrel

Abstract: Dasabuvir is mainly metabolized by cytochrome P450 (CYP) 2C8 and is predominantly used in a regimen containing ritonavir. Ritonavir and clopidogrel are inhibitors of CYP3A4 and CYP2C8, respectively. In a randomized, crossover study in 12 healthy subjects, we examined the impact of clinical doses of ritonavir (for 5 days), clopidogrel (for 3 days), and their combination on dasabuvir pharmacokinetics, and the effect of ritonavir on clopidogrel. Clopidogrel, but not ritonavir, increased the geometric mean AUC of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 42 publications
2
49
0
4
Order By: Relevance
“…The variation in the pharmacokinetic variables of gemfibrozil and its 1-O-glucuronide metabolite was smaller, only up to 2-fold. Consistent with previous DDI studies between clopidogrel or gemfibrozil and CYP2C8 substrates (Backman et al, 2002;Jaakkola et al, 2005;Tornio et al, 2014;Itkonen et al, 2016Itkonen et al, , 2018Itkonen et al, , 2019, no significant correlations were observed between the plasma concentrations of clopidogrel acyl-b-D-glucuronide or gemfibrozil 1-Oglucuronide and changes in desloratadine pharmacokinetics.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The variation in the pharmacokinetic variables of gemfibrozil and its 1-O-glucuronide metabolite was smaller, only up to 2-fold. Consistent with previous DDI studies between clopidogrel or gemfibrozil and CYP2C8 substrates (Backman et al, 2002;Jaakkola et al, 2005;Tornio et al, 2014;Itkonen et al, 2016Itkonen et al, , 2018Itkonen et al, , 2019, no significant correlations were observed between the plasma concentrations of clopidogrel acyl-b-D-glucuronide or gemfibrozil 1-Oglucuronide and changes in desloratadine pharmacokinetics.…”
Section: Resultssupporting
confidence: 89%
“…The resulting reduction in 3-hydroxydesloratadine:desloratadine AUC 0-71 h ratio by clopidogrel is consistent with an average 80% inhibition of CYP2C8 activity, assuming that clopidogrel had no effect on non-CYP2C8-mediated metabolism of desloratadine N-glucuronide nor on hydrolysis of either of the N-glucuronide intermediates. With respect to clopidogrel's CYP2C8 inhibition potency, this estimate is in accordance with recent findings that clopidogrel causes about 5-fold increases in exposures to repaglinide and dasabuvir, which are among the most sensitive CYP2C8 substrates identified so far (Tornio et al, 2014;Itkonen et al, 2019).…”
Section: Clopidogrel and Gemfibrozil Inhibit Desloratadine Metabolismsupporting
confidence: 91%
See 1 more Smart Citation
“…Several protocol strategies take into consideration the concomitant use of antithrombotic with antiviral therapies (especially with the antivirals liponavir and ritonavir), as this can affect choice and/or dosage of antiplatelet and anticoagulants. For antiplatelet agents, certain antivirals, especially lopinavir/ritonavir, may potentiate CYP3A4 or P‐gp inhibition, and as such there may be reduction in clopidogrel effects and increased effects of ticagrelor 52,53 . Therefore, these agents should be switched over to prasugrel if possible (unless there are contraindications such as prior stroke or transient ischemic attack) 53 .…”
Section: Introductionmentioning
confidence: 99%
“…3 Conversely, clopidogrel may not provide sufficient platelet inhibition during concomitant administration of lopinavir/ritonavir but this was not the case with prasugrel. 13,14 In case prasugrel cannot be used, testing guided approach with platelet function assays is strongly recommended. 11.…”
Section: Managing Acs During Covid-19 Infection: Do Not Follow the Trmentioning
confidence: 99%